Influence of Bobbin Tool Friction Stir Welding (BT-FSW) variants on the microstructure and properties of AA2060 and AA2196 aluminum alloys - Carvalho, Joana Amaral de (Universidade Federal de São Carlos, 2020)
In order to reduce total costs in aircrafts production, operation and maintenance, materials and processing techniques have been continuously further optimized. In this scenario, aluminum-lithium alloys have been studied due to its mechanical properties, low density and higher fatigue crack growth resistance compared to others aluminum alloys and steels. However, joining technologies usually applied in these alloys present limitations regarding uniformity, energy input and production costs. Since welding processes may not require any material additions such as rivets used in the mechanical fastening techniques conventionally used in joining aircrafts parts, it can contribute in saving structural weight. The aim of this research is to compare and understand the effect of two different methods of bobbin tool friction stir welding (BT-FSW), Self-Reacting BT-FSW (SRBT-FSW) and Stationary (upper) Shoulder BT-FSW (SSuBT-FSW) on the microstructure and mechanical properties of 3 mm thick aluminum-lithium alloys ( AA2060 and AA2196) plates in butt joint. In addition, the study of the influence of energy input on bobbin tool friction stir welding (BT-FSW) was evaluated to understand the effect of the parameters on the alloys. Defect free welds have been produced featuring a high-quality surface finish on the stationary side. In general, the self-reacting variant enabled welding with faster welding speeds than the SSuBT-FSW technique, which was the reason for lower energy input on SRBT-FSW. The influence of the processes on the microstructure and mechanical properties of different regions of the produced joint was evaluated by means of optical microscopy (OM), hardness testing and tensile testing. Differential scanning calorimetry (DSC) was performed to evaluate the influence of variants on precipitate evolution. Superior results were achieved welding AA2060 and AA2196 using SRBT-FSW- low energy input, reaching up to 78% of ultimate tensile strength of base metal.
Influência das variantes de soldagem por fricção e mistura utilizando a ferramenta bobbin tool (BT-FSW) na microestrutura e propriedades das ligas de alumínio-lítio AA2060 e AA2196
Keywords: Ligas de alumínio-lítio; Microestrutura; Propriedades mecânicas; Entrada de energia; Soldagem por fricção e mistura (FSW); Soldagem no estado sólido; Aluminum-lithium alloys; Bobbin Tool Friction Stir Welding (BT-FSW); Microstructure; Mechanical properties; Energy input; Friction Stir Welding (FSW); Solid state welding; AA2060; AA2196; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA